Integrating Cycled Enzymatic DNA Amplification and Surface-Enhanced Raman Scattering for Sensitive Detection of Circulating Tumor DNA - Miao, Xinxing; Fang, Qianqian; Xiao, Xiang; Liu, Sidi; Wu, Renfei; Yan, Jun; Nie, Baoqing; Liu, Jian (Frontiers in Molecular Biosciences, 2021)
Circulating tumor DNA (ctDNA) represents an emerging biomarker of liquid biopsies for the development of precision cancer diagnostics and therapeutics. However, sensitive detection of ctDNA remains challenging, due to their short half-life and low concentrations in blood samples. In this study, we report a new method to address this challenge by integrating cycled enzymatic DNA amplification technique and Au nanoparticle@silicon-assisted surface-enhanced Raman scattering (SERS) technique. We have demonstrated a reproducible identification of a single-base-mutated ctDNA sequence of diffuse intrinsic pontine gliomas (DIPGs), with the limit of detection (LOD) as low as 9.1 fM in the spiked blood samples. This approach can be used to analyze trace amounts of ctDNA in translational medicine for early diagnosis, therapeutic effect monitoring, and prognosis of patients with cancer.